2023
DOI: 10.1158/2159-8290.cd-22-0620
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of a Large Real-World Cohort of Small Cell Lung Cancer Identifies Distinct Genetic Subtypes and Insights into Histologic Transformation

Abstract: Small cell lung cancer (SCLC) is a recalcitrant neuroendocrine carcinoma with dismal survival outcomes. A major barrier in the field has been the relative paucity of human tumors studied. Here we provide an integrated analysis of 3,600 “real-world” SCLC cases. This large cohort allowed us to identify new recurrent alterations and genetic subtypes, including STK11-mutant tumors (1.7%) and TP53/RB1 wild-type tumors (5.5%), as well as rare cases that were human papillomavirus-positive. In our cohort, gene amplifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…5E). True paired cases of human LUAD before and after HT are limited, but some studies have compared unrelated de novo LUAD with transformed SCLC (T-SCLC) in an attempt to understand this phenomenon as it relates to de novo SCLC tumorigenesis ( 1 , 3 , 59 , 60 ). We reanalyzed a publicly available cohort and could demonstrate that Myc target genes were differentially increased in T-SCLC as compared with LUAD, suggesting that Myc may have a role in facilitating HT in a clinical setting (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5E). True paired cases of human LUAD before and after HT are limited, but some studies have compared unrelated de novo LUAD with transformed SCLC (T-SCLC) in an attempt to understand this phenomenon as it relates to de novo SCLC tumorigenesis ( 1 , 3 , 59 , 60 ). We reanalyzed a publicly available cohort and could demonstrate that Myc target genes were differentially increased in T-SCLC as compared with LUAD, suggesting that Myc may have a role in facilitating HT in a clinical setting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study relied on putative HT samples in which a LUAD oncogenic driver was detected in a histologically confirmed SCLC. When compared to de novo SCLC, these cases were enriched for mutations that activate the PI3K signaling pathway ( 61 ). Consistent with this result, we found that loss of Pten or activation of Pik3ca was sufficient to break a barrier in the AT2 lineage to transformation by Myc but insufficient to lead to neuroendocrine transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale genomic analysis of lung tumors has identified many recurrent gene mutations with unclear roles in tumor development ( [1][2][3]. Therefore, it is essential to generate models that facilitate the rapid introduction of sets of mutations into lung tissue to assess their importance in disease progression.…”
Section: Introductionmentioning
confidence: 99%